2021
DOI: 10.1177/1357633x211041859
|View full text |Cite
|
Sign up to set email alerts
|

Optimising specialist geriatric medicine services by telehealth

Abstract: Telehealth can effectively increase access to specialist care and reduce the need for travel. The Geri-Connect service was established in 2017 to support people living in residential aged care facilities in regional Victoria, Australia. Using the Model for the Assessment of Telemedicine, an evaluation of the Geri-Connect service identified service activity patterns and factors associated with uptake. Service activity from 2017 to 2020 and 10 semi-structured, key stakeholder interviews were captured and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Of this sample of the studies considered, eleven were retrospective, three prospective, and eleven were unspecified (Tables 1 and 2). All articles included different clinical diseases and medical disciplines: dermatology [23][24][25][26], sexual health [27], psychiatry [28], neurology [29,30], geriatrics [31], ophthalmology [32][33][34][35], physiology [36], orthopaedics [37][38][39], respiratory failure [40], paediatric diabetic [41], injury/illness [42], mixed [43,44], radiology [45], and atrial fibrillation [46], N.S. [47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of this sample of the studies considered, eleven were retrospective, three prospective, and eleven were unspecified (Tables 1 and 2). All articles included different clinical diseases and medical disciplines: dermatology [23][24][25][26], sexual health [27], psychiatry [28], neurology [29,30], geriatrics [31], ophthalmology [32][33][34][35], physiology [36], orthopaedics [37][38][39], respiratory failure [40], paediatric diabetic [41], injury/illness [42], mixed [43,44], radiology [45], and atrial fibrillation [46], N.S. [47].…”
Section: Resultsmentioning
confidence: 99%
“…Services treated by studies were different: 16 were telecounselling, four were telemonitoring [40,[44][45][46], and five were mixed [26,31,37,38,41]: telecounselling + telemonitoring.…”
Section: Telemedicine Servicementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the lack of a supportive infrastructure, as mentioned by Seiffert et al [ 18 ], was also the main barrier for implementation as mentioned by our participants, which is confirmed by the study of Haydon et al who describe recommendations regarding infrastructure for adoption of VC use in geriatric medicine. [ 19 ]. While COVID-19 served as a catalyst for the adoption of telemedicine in some geriatric clinical settings [ 20 ], this was less so among our geriatric outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that a multidisciplinary team involving nurses may facilitate future treatment and rehabilitation in geriatric patients with cardiovascular disorders [ 86 ]. Dedicated centralized team leaders are best suited in implementing the guidelines for residential aged care facility residents requiring specialized geriatric care via telehealth and counselling [ 87 ]. It has also been observed that the enthusiastic involvement of pharmacists in deprescription has proved beneficial in the case of elderly patients in all types of resource settings [ 88 ].…”
Section: Management Planmentioning
confidence: 99%